As capabilities profissionais para o bem público valiosas aos egressos de stricto sensu das Universidades Comunitárias do sul do Brasil - Fortunato, Raquel Paula (2021)
This dissertation seeks to understand the Capability Approach according to the Senian and Nussbaumian approach and the operationalization of this quality-of-life assessment structure. Focusing on the beneficial role of education for human development and knowledge as a public good, the provision of which is essential to promote the well-being of individuals, the study draws on and complements its theoretical framework with guidance from the Public Good Professional Capabilities Index by Walker and McLean (2013). Given the contributions in the literature on the subject, the main objective of this study is to verify whether graduates from community institutions are committed to human development, democratic values, and social justice, as well as its constitutive and formative principles. Therefore, this dissertation seeks to know if the masters and doctors from community universities recognize the professional capabilities for the public good as essential or valuable in their way of being and doing professionally and promote and expand these capabilities to society. For that, explores the normative index with these scientists and professors, trying to identify if they act or are willing to for the public good, to reduce the inequalities and injustices in the world since it is recommendable or socially desirable that they are committed to the public issues of society. This identification is because such commitment must be congruent with the constitutive principles of the community institution and with the central elements of the capability approach. According to the purposes of the study, we built an appropriate methodological path for qualitative research. To this end, we were guided by the propositions of Neuman (2014) and created a ten-step sequence to conduct the investigation. Using the Delphi method, we submitted the Walker and McLean (2013) index to critical scrutiny by experts and adapted the list to the study context. Once the index was adjusted, we built a unique and legitimate assessment model with six “pro-public-good” professional qualifications for postgraduate studies at Community Higher Education Institutions. The model was applied to three community universities and seven postgraduate programs in different professional fields. Data were produced through interviews carried out with graduates (masters and doctors) and were analyzed and interpreted with the aid of discursive practices and in the light of existing theory on the subject. The results show that postgraduates recognize the set of professional qualifications for the public good as essential to the constitution and training of the good professional. However, they also recognize that they still do not fully expand these capabilities and can produce more goods and services relevant to society since they perceive themselves as responsible agents and capable of promoting well-being. This finding indicates that the postgraduate programs of Community Higher Education Institutions investigated contribute and develop training and preparation for the public good of their graduates. Finally, we understand that the capability approach and Public Good Professional Capabilities Index can become a powerful tool for the Brazilian National Graduate Program to achieve its goals and strengthen its social role. We also believe that this study can be useful to community institutions, especially to support their historic mission of regional development and social commitment.